MreB and MurG as scaffolds for the cytoplasmic steps of peptidoglycan biosynthesis. (4th July 2013) - Favini‐Stabile, Sandy; Contreras‐Martel, Carlos; Thielens, Nicole; Dessen, Andréa; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary Peptidoglycan is a major determinant of cell shape in bacteria, and its biosynthesis involves the concerted action of cytoplasmic, membrane‐associated and periplasmic enzymes. Within the cytoplasm, Mur enzymes catalyse the first steps leading to peptidoglycan precursor biosynthesis, and have been suggested as being part of a multicomponent complex that could also involve the transglycosylase MurG and the cytoskeletal protein MreB. In order to initialize the characterization of a potential Mur interaction network, we purified MurD, MurE, MurF, MurG and MreB from Thermotoga maritima and characterized their interactions using membrane blotting and surface plasmon resonance. MurD, MurE and MurF all recognize MurG and MreB, but not each other, while the two latter proteins interact. In addition, we solved the crystal structures of MurD, MurE and MurF, which indicate that their C‐termini display high conformational flexibilities. The differences in Mur conformations could be important parameters for the stability of an intracytoplasmic murein biosynthesis complex.